2019
DOI: 10.3390/agronomy9110715
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Enrichment Combined with Supplemental Light Improve Growth and Quality of Plug Seedlings of Astragalus membranaceus Bunge and Codonopsis lanceolata Benth. et Hook. f.

Abstract: Astragalus membranaceus Bunge and Codonopsis lanceolata Benth. et Hook. f. are two medicinal species used to remedy inflammation, tumor, and obesity in Eastern medicine. Carbon dioxide (CO2) and supplemental lighting are two methods to enhance the growth, yield, and quality of crops. However, few studies have focused on the synergistic effects of CO2 and the supplemental light source on plug seedlings of medicinal species. In this study, uniform seedlings were grown with no supplemental light (the control) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The trends in soluble proteins and carbohydrates in the cuttings were similar to those of the root biomass and root activities ( Figure 6 and Table 2). Light-especially red and blue-can stimulate photosynthetic enzyme activities and improves stomatal opening, which is the foundation of photosynthesis [67]. Compared to HPS lamps, MH and LED-mix provide a higher percentage of red and blue lights, which resulted in a greater increase of soluble proteins and carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…The trends in soluble proteins and carbohydrates in the cuttings were similar to those of the root biomass and root activities ( Figure 6 and Table 2). Light-especially red and blue-can stimulate photosynthetic enzyme activities and improves stomatal opening, which is the foundation of photosynthesis [67]. Compared to HPS lamps, MH and LED-mix provide a higher percentage of red and blue lights, which resulted in a greater increase of soluble proteins and carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…It is a parameter that determines the amount of photoassimilates produced and affects who is growth, development, and productivity [37]. In general, it is assumed that LA and biomass accumulation in crops may be affected by some factors, such as light quality and radiation intensity, plant nutrition, substrate type, and container design and volume [38][39][40][41].…”
Section: Leaf Area (La)mentioning
confidence: 99%
“…Previous studies have concluded that plasma membrane H + -ATPase plays a critical role in regulating stomatal opening [114] and plays a crucial and primary role in regulating plant growth [115] and responses to environmental stimuli [116]. The opening and closing of stomatal guard cells are regulated by phototropins present in stomatal guard cells in response to blue light stimuli [117] to allow the uptake of CO2 to facilitate photosynthesis [112,118], which further leads to transpirational loss of water through leaves. In order to minimize the water loss, guard cells tend to close the stomatal pore during heavy sunlight or other high light conditions.…”
Section: Photosynthetic Efficiency In Plants Under Ledsmentioning
confidence: 99%